(untitled) (Bangladesh Journal of Medicine, 2026)
Background: Dengue poses a major public health burden in Bangladesh; particularly during seasonal outbreaks. The 2024 outbreak saw a rise in moderate to severe cases. The aim of study to assess the clinical features, hematological trends, treatment strategies, and outcomes of hospitalized dengue patients during the 2024 outbreak in Dhaka. Methods: A cross sectional study of 935 serologically confirmed dengue patients was conducted at Z.H. Sikder Women’s Medical College & Hospital,Dhaka,Bangladeh from March to November 2024. Patients were classified into mild, moderate, and severe groups based on WHO criteria. Clinical data, laboratory trends, and treatment responses were analyzed. Results: Mean age was 31.7±4.8years; 60% were male. Common symptoms were included fever (100%), headache (86.9%), and vomiting (76%). Severe dengue accounted for 28.1% of cases, with bleeding in 28% and thrombocytopenia in 89.7%. Platelet count nadir occurred on Day 5. Elevated SGPT and bleeding were significant mortality predictors. Corticosteroid use in severe cases was associated with clinical improvement. No deaths were reported. Conclusion: Early diagnosis and severity-based management, including selective steroid use, can improve outcomes in dengue patients. Further trials are needed to validate corticosteroid therapy in severe cases. Bangladesh J Medicine 2026; 37(1): 21-27